2015
DOI: 10.1186/s12885-015-1584-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes regarding medical research studies among patients with breast cancer and gynecological diseases

Abstract: BackgroundMedical research studies are becoming increasingly important for optimizing the prevention, diagnosis and treatment of illnesses. Participation in research studies can have many benefits for patients. In randomized and controlled clinical studies, they can receive the best possible medical care currently available. However, only a small proportion of patients nowadays are treated within the framework of medical research. The primary endpoint of this study was to discover what level of knowledge patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
7
50
1
Order By: Relevance
“…These findings are consistent with clinical observations, where high infiltration of MC has been observed in human colon cancer. 1013,15–17 MC migration toward Caco2 was observed solely SCF-dependent. SCF is an important growth factor for MC, but also induces chemotaxis and survival.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with clinical observations, where high infiltration of MC has been observed in human colon cancer. 1013,15–17 MC migration toward Caco2 was observed solely SCF-dependent. SCF is an important growth factor for MC, but also induces chemotaxis and survival.…”
Section: Discussionmentioning
confidence: 91%
“…7 MC density in CRC tissues is positively associated with poor clinical outcomes in patients 1013,15,17 and decreased intestinal tumor growth has been observed in MC-deficient mice. 28,29 Our study further provides experimental evidence that primary human MC promote colon cancer growth by stimulating production of pro-tumorigenic mediators in a bidirectional manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Studies found that stomatin and its family members participate in the occurrence of malignant tumors, and that SLP-2 is overexpressed in choriocarcinoma placental cells, ovarian cancer, and cervical cancer; however, research on SLP-2 in liver cancer is rarely conducted. [20][21][22] We found for the first time that inhibiting the expression of SLP-2 gene in liver cancer cells could inhibit NF-kB, reduce the inflammatory response, and downregulate the expression levels of MMP-2 and MMP-9 and therefore inhibit the migration and invasion of liver cancer cells. 23 The purpose of this study was to investigate the effect of SLP-2 on liver cancer cells, and the data showed that the expression level of SLP-2 gene in liver cancer cells was higher than that in human normal liver cells, suggesting that SLP-2 is possibly involved in the growth of hepatoma cells.…”
Section: Discussionmentioning
confidence: 91%
“…The inclusion criteria for the postoperative radiotherapy and chemotherapy group (PORCT) groups and the postoperative chemotherapy group (POCT) groups were the same, as follows: complete surgical resection through either lobectomy or pneumonectomy; systematic nodal dissection, a minimum of three N2 stations sampled or complete dissection (one of which must be the subcarinal station); and histologically proven NSCLC of stage pT1-3N2M0 (according to the TNM classification in the UICC 7th ed). 13,14 Patients who received neoadjuvant therapy (chemotherapy and/or radiotherapy), showed evidence of metastatic disease or presented with previous malignancy were excluded. Patients with EGFR mutations receiving tyrosine kinase inhibitor (TKI) treatment after surgery were also excluded.…”
Section: Methods and Materials Patient Selectionmentioning
confidence: 99%